Perspective trends of topical therapy of patients with psoriasis - Alexander S. Zhukov; Vladislav R. Khairutdinov; Alexey V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Topical medications are used to treat not only limited, but also common forms of the disease. Currently prescribed external anti-inflammatory drugs have a low selectivity of action, which does not allow achieving a long-term and pronounced clinical effect without the development of undesirable phenomena. This review presents new options for the use of methotrexate in modern topical forms (AuNPs-3MPS), which make it possible to reduce the incidence of adverse events with a high efficiency of therapy. Shown is an innovative drug that blocks resident memory cells (PAP-1), which will influence the course and relapses of the disease, and possibly even lead to the cure of the patient from psoriasis. A new direction has been described inhibition of serine proteases (ER143, AAN-16) and thus inhibition of IL-36-mediated inflammation, which will allow controlling the inflammatory process in psoriasis in the early stages of its development. In addition, a number of drugs are shown whose action is based on blocking intracellular signaling pathways, which leads to inhibition of the development of the inflammatory response and resolution of psoriatic eruptions: inhibitors of Janus kinases (tofacitinib), transcription factor Stat3 (rS3-PA), secondary messenger of signals (SIS3), phosphodiesterase 7 (ASB16165) and 4 (AN-2728/crisaborol), ROR transcription factor (PF-06763809), phospholipase A2 (AVX001), hydrolases (DZ2002). The results of preclinical and initial stages of clinical trials with an assessment of the safety and tolerability of the studied substances are presented. Based on the review, the advantages and disadvantages of the proposed drugs are characterized. Topical therapy with a selective effect on the key links in the development of psoriasis will increase the effectiveness of treatment and reduce the frequency of unwanted effects.